2012
DOI: 10.1093/abbs/gmr104
|View full text |Cite
|
Sign up to set email alerts
|

Virion protein 16 induces demethylation of DNA integrated within chromatin in a novel mammalian cell model

Abstract: DNA methylation and demethylation play important roles in mediating epigenetic regulation. So far, the mechanism of DNA demethylation remains elusive and controversial. Here, we constructed a plasmid, named with pCBS-luc, that contained an artificial CpG island, eight Gal4 DNA-binding domain binding site, an SV40 promoter, and a firefly luciferase reporter gene. The linearized pCBS-luc plasmid was methylated in vitro by DNA methyltransferase, and transfected into the HEK293 cells. The stable HEK293 transfectan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…To determine AAP activity within silenced chromatin, we targeted AAP fusion proteins (Supplementary Figure S2) to a chromosomal luciferase reporter that had been previously targeted by Polycomb repressive complexes (PRCs). The AAP open reading frames (ORFs) encode catalytic subunits or full length proteins (Supplementary Figure S2) that have been shown to support an epigenetically active state in several prior studies [39,40,44,46,[58][59][60][61][62][63][64]. All of these ORFs exclude DNA binding and histone binding domains, except for the ORF encoding FOXA1, which has a catalytic domain that requires histone interactions.…”
Section: Identification Of Fusion Activators With Robust Activity Witmentioning
confidence: 99%
“…To determine AAP activity within silenced chromatin, we targeted AAP fusion proteins (Supplementary Figure S2) to a chromosomal luciferase reporter that had been previously targeted by Polycomb repressive complexes (PRCs). The AAP open reading frames (ORFs) encode catalytic subunits or full length proteins (Supplementary Figure S2) that have been shown to support an epigenetically active state in several prior studies [39,40,44,46,[58][59][60][61][62][63][64]. All of these ORFs exclude DNA binding and histone binding domains, except for the ORF encoding FOXA1, which has a catalytic domain that requires histone interactions.…”
Section: Identification Of Fusion Activators With Robust Activity Witmentioning
confidence: 99%
“…Numerous studies have shown that many proteins are involved in DNA active demethylation, including Gadd45a [9], Elp3/KAT9 [10], AID/APOBEC [11][12][13][14], MBD4 [15,16], virion protein16 (Vp16) [17], SMUG1 [18], TGF-b [19], and FGF [20]. TETs and thymine DNA glycosylase-mediated (TDG-mediated) active demethylation are considered a classic pathway [21][22][23][24][25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…to a chromosomal luciferase reporter that had been previously targeted by Polycomb repressive complexes (PRCs). The AAP open reading frames (ORFs) encode catalytic subunits or full length proteins (SupplementaryFigure S2) that have been shown to support an epigenetically active state in several prior studies(42,43,47,49,(61)(62)(63)(64)(65)(66)(67) . All of these ORFs exclude DNA binding and histone binding domains, except for the ORF encoding FOXA1 which has a catalytic domain that requires histone interactions.…”
mentioning
confidence: 99%